Intriguing interactions of triazolyl organosilane with copper (II) ion, blue copper protein, and silica nanoparticles: Spectral and theoretical approach. (5th October 2022) - Singh, Gurjaspreet; Kaur, Jashan Deep; Pawan,; Priyanka,; Mohit,; Devi, Anita; Gupta, Sofia; Thakur, Yamini; Singh, Kamal Nain
Abstract : In this manuscript, a concise library of 2‐Amino‐4‐chlorophenol‐based organosilanes 5(a‐c) was designed and synthesized by employing a multistep strategy and characterized with the help of NMR ( 1 H and 13 C) spectroscopic and mass spectrometry techniques. The silica nanoparticles loaded with 5a have been successfully synthesized and confirmed with the help of various techniques. Further, the interaction of probes 5a and its hybrid silica nanoparticles (A‐NPs) have been investigated towards various metal ions and exhibited favorable selectivity towards Cu 2+ ions over other common metal ions in methanol with both colorimetric and fluorimetric read‐outs. The binding of probes 5a and A‐NPs with Cu 2+ can be monitored by change of color in daylight and also by turn‐off fluorescence response in UV light. The sensing mechanism is ascribed to paramagnetic nature of Cu 2+ ion leading to ligand to metal charge transfer and, hence, shows chelation enhanced fluorescence quenching (CHEQ) effect in the vicinity of ligands 5a and A‐NPs. The results demonstrated that the hybrid nanocomposites (A‐NPs) has even lower limit of detection and higher binding affinity as compared to probe 5a. The possible mechanism of 1:1 binding of 5a with Cu 2+ could be substantiated by the density functional theory. Thus, this facile and appropriate sensing strategy may serve as a promising tool for selective and sensitive detection of Cu 2+ ions. Moreover, the molecular docking studies provide valuable information regarding the interaction of compound 5a with the blue copper protein (plastocyanin). Hence, the current investigation provides a new avenue to design more potent organosilane analogs. Abstract : 2‐Amino‐4‐chlorophenol‐based Triazolyl organosilanes 5(a‐c) were synthesized by employing a multistep strategy. The surface of silica nanoparticles was modified by fabrication of compound 5a on it. Moreover, the probe 5a showed interactions with Cu (II) and blue copper protein (plastocyanin).